Iron (Fe) bioavailability and the distribution of anti-Fe nutrition biochemicals in the unpolished, polished grain and bran fraction of five rice genotypes - Chanakan Prom-U-Thai (2018)
Iron (Fe) bioavailability in unpolished, polished grain and bran fraction of five rice genotypes with a range of Fe contents was measured by in vitro digestion and cultured Caco-2 cells of cooked grain. There was a significant difference in Fe bioavailability among the five rice genotypes tested, in both the unpolished and polished grain. The range of Fe bioavailability variation in polished rice was much wider than that of unpolished, suggesting the importance of using Fe levels and bioavailability in polished rice grain as the basis for selecting high-Fe rice cultivars for both agronomic and breeding purposes. Milling and polishing the grain to produce polished (or white) rice increased Fe bioavailability in all genotypes. Iron bioavailability in polished rice was high in the UBON2 and Nishiki, intermediate in both IR68144 and KDML105, and low in CMU122. All genotypes had low bioavailability of Fe in bran fraction compared to unpolished and polished grain, except in CMU122. CMU122 contained the lowest level of bioavailable Fe in unpolished and polished grain and bran, because of the dark purple pericarp colored grain and associated tannin content. The level of bioavailable Fe was not significantly correlated with grain Fe concentration or grain phytate levels among these five genotypes tested. The negative relationship between Fe bioavailability and the levels of total extractable phenol was only observed in unpolished (r = -0.83**) and bran fraction (r = -0.50*). The present results suggested that total extractable phenol and tannin contents could also contribute to lowering bioavailability of Fe in rice grain, in addition to phytate. © 2006 Society of Chemical Industry.